Manganese(i)-catalyzed dehydrogenative borylation of terminal alkynes - Ghanwat, Pratiksha B.; Bora, Debashree; Pandya, Rinu; Vanka, Kumar; Saha, Biswajit; Sen, Sakya S. (Dalton Transactions, 2025)
Compounds containing carbon-boron bonds serve as valuable intermediates for constructing more complex molecules by transforming these bonds into other carbon-element bonds. The catalytic dehydrogenative borylation of carbon-hydrogen bonds using HBpin presents an appealing method for synthesizing carbon-boron bonds. While this approach has been extensively explored with noble metals for various types of carbon-hydrogen bonds, its application with manganese-based catalysts remains rare. This study explores a dehydrogenative borylation process employing an Earth-abundant transition metal catalyst, FcbpyMn(CO)3Br (Mn(i)), in combination with HBpin under mild conditions. Arylalkynes featuring electron-withdrawing, electron-donating, and heteroaryl substituents yielded good to excellent results. Thorough DFT calculations were performed to understand the mechanism.